Variability Among Isolates of Alternaria Porri Causing Blight of Niger From Different Geographical Regions of India (Journal of Plant Disease Sciences, 2018)
Alternaria blight is the major constraint for niger production. Five isolates of Alternaria porri from three states were studied for cultural, morphological and pathogenic characteristics. The isolates showed high level of variability in vitro in respect of conidia length, width, and beak and without beak, number of septa, type of growth, pigmentation and pathogenic characteristics. Maximum colony diameter was observed in Ap-1 of Udaipur (88.22 mm) and minimum recorded in Ap-5 (79.22 mm) after 7 days of incubation. Maximum number of conidia i.e.14.68×103 conidia/ mm2, were recorded in Ap-1 and minimum sporulation 10.46 ×103 conidia / mm2 was in Ap-5 of Vanrasi . The colony character i.e., margin/shape and colour of the culture of different isolates varied from cottony woolly growth, aerial at centre, concentric zonation, whitish margin, white, dark greyish in color later turned dark black in Ap-1. While Ap-5 showed felty mycelial growth, with light grayish black with whitish margin and isolates also differed in the size of the conidia the largest conidia with beak was of Ap-1, 98-112 × 26-39 µm. Whereas, smallest size of conidia is Ap-5, 75-100 × 19-25µm . Similarly, the isolates differed in the number of horizontal and vertical septa, where average number of horizontal and vertical septa were 3-9 and 0-5 in Ap-1 and minimum in Ap-5. The minimum latent period was observed in isolate Ap-1 with 39 hr with 49.51% PDI followed by 45 hr in isolate Ap 2 with 45.25 % PDI and longest latent period of 62 hr and 37.6% PDI was recorded in isolate Ap-5.
Keywords: Alternaria porri; Niger; Cultural; Morphological; Pathogenic; Variability